How Purpose-Driven Organizations Influenced Corporate Actions and Employee Trust during the Global COVID-19 Pandemic. Issue 3 (27th May 2022) - Qin, Yufan Sunny; DiStaso, Marcia W.; Fitzsimmons, Alexis; Heffron, Eve; Men, Linjuan Rita
ABSTRACT: The COVID-19 global pandemic drove many companies to reevaluate their approach to business and, as a result, some focused their efforts on leading with purpose. Purpose is an organization's fundamental goal that goes beyond profit maximization. It is an all-encompassing principle that guides everything the organization does and determines its strategies. Effective strategic communication is an essential element of purpose as it can empower employees to align their personal goals with organizational values and thus more closely identify with their organization. However, while the benefits of purpose are frequently proclaimed in practical literature, the impact of communicating purpose on employee outcomes remains unexplored in strategic communication research. To address this critical research gap, this study examined why and how communicating purpose could be an effective tactic in strategic communication. Specifically, this study introduced the concept of purpose and examined how purpose directed organizations' actions in response to COVID-19 as well as the impact of purpose on employees' organizational identification and trust. The findings offer practical implications regarding the importance of strategic communication about purpose in terms of building employee organizational identification and trust during times of change.